Clinical utility of MODAPTS during work assessment: Perceptions of South African occupational therapists. - Buys, Tania Lee; Harmse, Suzanne; Slawson, Caitlin Christina; Rapolai, Boitumelo Thamirah; Rapotu, Kwena Dorah; Furniss, Sian Gabrielle; Jordaan, Karma (South African Journal of Occupational Therapy, 2024)
Introduction: Clinical utility is an important attribute in selecting an assessment tool. The study aimed to determine the perceptions of South African occupational therapists of the clinical utility of Modular Arrangement of Predetermined Time Standards (MODAPTS) work samples when assessing a client's work ability. The research objectives were to determine whether MODAPTS is perceived to be credible, practical, useful, and easy to use. Methodology: A quantitative, cross-sectional, descriptive research design was used. Non-probability sampling with elements of voluntary response- and snowball sampling was used to recruit respondents. An electronic questionnaire was developed using Qualtrics, which was distributed electronically via the Occupational Therapy Association of South Africa, WhatsApp and Telegram. Results: Data were based on 52 completed questionnaires, analysed through descriptive statistics. MODAPTS was perceived as practical, useful, credible, and asy to use in practice. Main barriers to the use of MODAPTS included the timeliness of developing work samples, lack of MODAPTS training, and having other more useful and reliable assessment tools. Experienced occupational therapists used MODAPTS more often than inexperienced occupational therapists. Conclusion: Clinical utility of work samples developed using MODAPTS has been confirmed. This supports the use of work samples developed using MODAPTS as part of work assessments as a cost-effective, practical tool.